Monitoring severe acute maternal morbidity across Europe: A feasibility study. Issue 4 (9th September 2019) - Chantry, Anne A.; Berrut, Sylvan; Donati, Serena; Gissler, Mika; Goldacre, Raphael; Knight, Marian; Maraschini, Alice; Monteath, Kirsten; Morris, Anna; Teixeira, Cristina; Wood, Rachael; Zeitlin, Jennifer; et al.
Abstract: Background: Monitoring severe acute maternal morbidity (SAMM) appears essential for optimising care and informing health care policies, especially given changes in obstetric practices and mother profiles. International comparisons can identify areas where improvement is needed, but the comparability of indicators must be evaluated. Objective: To assess the feasibility of monitoring SAMM using common definitions from hospital discharge databases across Europe. Methods: We used hospital discharge data in eight countries (2 826 868 deliveries) to identify women with SAMM among all hospitalisations of women of reproductive age admitted for antenatal or delivery care. Five SAMM indicators were investigated: eclampsia, septicaemia, hysterectomy, hysterectomy associated with a diagnosis of obstetric haemorrhage, and red blood cell (RBC) transfusion associated with a diagnosis of obstetric haemorrhage. Between‐country variation was described, by the ratio of the highest to lowest rates, while external validation was assessed by comparing with population‐based studies on maternal morbidity. Results: Ratios for hysterectomy and red blood cell (RBC) transfusion in the context of obstetric haemorrhage were 1:2.1 and 1:3.5, respectively. High values of hysterectomy and low values of transfusion were both consistent with high maternal mortality from haemorrhage (France, Italy, Portugal). Ratios across countries were relatively low for eclampsia (1:3.4) but very high for septicaemia (1:22.5). Compared to population‐based morbidity estimates, eclampsia was over‐reported in hospital databases whereas the two indicators of severe haemorrhage had good external validity. Conclusions: In association with diagnosis codes indicating obstetric haemorrhage, hysterectomy and RBC transfusion appear to be good candidates for surveillance of maternal morbidity in Europe.